An attempt of a new motion measurement method for alpine ski turns using inertial sensors - Kondo, A.; Doki, H.; Hirose, K. (Procedia Engineering, 2012)
This paper proposes the motion measurement method of skiing turn using inertial sensor. This method calculates the joint angle of the skier gliding on the actual snow field using the information from the inertial sensor units. The sensor fusion estimates the 3D posture (Roll-Pitch-Yaw angle) of local coordinate system compensated drift error of gyro sensor output using acceleration sensor output. The unscented Kalman filter is used to apply the sensor fusion. The joint angle is calculated by applying inverse kinematics to the 3D posture. In this study, the measurement experiment was conducted by the skier gliding on the actual snow field. The inertial sensor units were attached to body segments of skier. We obtained the joint angle of skier (Lumber, hip, knee and ankle). The results of motion analysis represented the major features of skiing turn, and the effectiveness of our proposed method was indicated.